2016
DOI: 10.1007/s00265-016-2215-y
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent behavior and alternative behavioral strategies in brown trout (Salmo trutta L.) fry

Abstract: Animals generally adjust their behavior in response to bodily state (e.g., size and energy reserves) to optimize energy intake in relation to mortality risk, weighing predation probability against the risk of starvation. Here, we investigated whether brown trout Salmo trutta adjust their behavior in relation to energetic status and body size during a major early-life selection bottleneck, when fast growth is important. Over two consecutive time periods (P1 and P2; 12 and 23 days, respectively), food availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 91 publications
4
31
0
Order By: Relevance
“…The higher preference score for active individuals seen in the binomial choice test may give an indication of this pattern. As repeatable individual differences in activity have been shown in juvenile brown trout (Adriaenssens & Johnsson, ; Näslund & Johnsson, ), the higher interspecific association tendency might give active individuals a feeding disadvantage due to increased competition with aggregated brook trout compared to less active individuals showing less interspecific association.…”
Section: Discussionmentioning
confidence: 90%
“…The higher preference score for active individuals seen in the binomial choice test may give an indication of this pattern. As repeatable individual differences in activity have been shown in juvenile brown trout (Adriaenssens & Johnsson, ; Näslund & Johnsson, ), the higher interspecific association tendency might give active individuals a feeding disadvantage due to increased competition with aggregated brook trout compared to less active individuals showing less interspecific association.…”
Section: Discussionmentioning
confidence: 90%
“…), the fish are considered to be trialled in a stressed state. Previous studies on juvenile brown trout have shown that activity in this type of test is repeatable within individuals (Adriaenssens & Johnsson ; Näslund & Johnsson ) and covaries positively with behaviours in the wild, such as movement activity after displacement (Závorka et al. ) and diurnal activity (Závorka et al.…”
Section: Methodsmentioning
confidence: 93%
“…Experimental design, statistical rigor, and other insights from social psychology, too, have enriched the field of PNI. Moving forward, those studying relationships between the immune system and the social behavior will face several challenges, including situating findings from PNI into current social psychological and evolutionary biological theories (e.g., state‐dependent decision making; Higginson et al, ; Näslund & Johnsson, ; McNamara & Houston, ), establishing causal pathways using experimental designs (e.g., endotoxin; Eisenberger, Berkman, et al, ; Eisenberger, Inagaki, et al, ) and finding suitable outlets for publication. In overcoming these challenges, however, such research is positioned to transform our understanding of human psychology and behavior.…”
Section: Discussionmentioning
confidence: 99%